Ionomer assessment techniques by microfiltration tests - Zumárraga Paredes, María José (2017)
Objectives: An in vitro study which was assessed by testing the appropriate microfiltration protocol using a conventional ionomer cement with sandwich technique in Black’s cavities class I. Methods: 60 human premolars, which underwent standardized cavities. These were randomly divided into 4 groups of 15 teeth each: G1 had IVC Ketac Molar Easymix and G3 had Ionofil Plus respectively to the edge of the cavity and then to wear them in 24 hours, leaving 1mm cavity base and subsequently using phosphoric acid on both enamel and dentin. In G2 and G4 both were simultaneously conditioned with polyacrylic on dentin and phosphoric acid on enamel, followed by washing, drying and 1mm placement of IVC Ionofil Plus and Ketac Molar Easymix respectively. All groups received two layers of adhesive OneCoat S Bond Coltene, light cured for 30 seconds, finally Brillant Coltene resin was applied in an incremental technique polymerizing each layer for 20 seconds. After final polishing of the dental restorations, the premolars became subjected to 10,800 cycles of thermocycling for future placement in methylene blue and measuring the microfiltration with the use of a stereo microscope. Results: There were no differences in the number of steps, but did indicate a minimal discrepancy as to the material used, whereas Ketac Molar Easymix showed a lower degree of filtration. The results were corroborated with SEM images. Conclusions: The analysis made it possible to determine no difference between the two  ionomer materials placed using a closed sandwich technique in one or two steps